Antibacterial behaviour of surface modified composite polyamide nanofiltration (NF) membrane by immobilizing Ag-doped TiO2 nanoparticles. Issue 28 (18th December 2020) - Habib, Zunaira; Khan, Sher Jamal; Ahmad, Nasir Mehmood; Shahzad, Hafiz Muhammad Aamir; Jamal, Yousuf; Hashmi, Imran
ABSTRACT: Modification of active membrane surface is an auspicious way to enhance the membrane performance. In our study, a commercially available composite polyamide Nanofiltration (NF) membrane was modified by immobilizing silver doped TiO2 (Ag–TiO2 ) nanoparticles. Ag–TiO2 with different nanoparticles concentration (0.05, 0.1, and 0.5 wt. %) were coated on the surface of the membrane by a dip coating method. The evidence of successful coating was evaluated by Scanning Electron Microscopy coupled with Energy Dispersive Spectroscopy and Atomic Force Microscopy images. Moreover, the Attenuated Total Reflectance Fourier Transform Infrared Spectroscopy (ATR-FTIR), contact angle measurement and permeation tests were carried out in order to evaluate the membrane performance after coating. The antifouling property of the modified membrane was evaluated for Gram-positive ( Bacillus subtilis ) and Gram-negative ( Escherichia coli ) bacteria by colony counting method. The results indicated that the modified membranes keep efficient antibacterial efficacy against both types of bacteria. The bacterial growth reduced approximately 93% and 91% on the modified membrane as compared to the unmodified membrane for E.coli and B.subtilis, respectively. Ag–TiO2 nanoparticles imbedded nanofiltration membranes inhibit the biofilm formation and facilitate in cleaning membrane surface without using excessive chemical agents. GRAPHICAL ABSTRACT: UF0001